2020
DOI: 10.1155/2020/1065202
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Rehabilitation Effect of Postoperative Lower-Limb Training on the Patients Undergoing OLIF Surgery: A Retrospective Study

Abstract: Background. In this study, it was aimed to investigate the clinical rehabilitation effect of lower-limb training on the patients that undergo oblique lumbar interbody fusion (OLIF) procedures. Methods. The eligible participants undergoing OLIF procedures between 01/2017 and 07/2019 were identified. All the patients underwent one-segment fusion operation (L3-4 or L4-5). Based on whether the participants received postoperative rehabilitation training, they were divided into two groups: intervention group and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
5
14
0
Order By: Relevance
“…A previous study showed that postoperative lower extremity rehabilitation exercise can effectively accelerate patients' health recovery from the oblique lumbar interbody fusion surgery and increase their satisfaction [16], which was similar with our results. Another study has shown that rehabilitation nursing combined with conservative treatment can shorten the healing period and improve functional recovery in elderly compression fracture patients [17].…”
Section: Discussionsupporting
confidence: 91%
“…A previous study showed that postoperative lower extremity rehabilitation exercise can effectively accelerate patients' health recovery from the oblique lumbar interbody fusion surgery and increase their satisfaction [16], which was similar with our results. Another study has shown that rehabilitation nursing combined with conservative treatment can shorten the healing period and improve functional recovery in elderly compression fracture patients [17].…”
Section: Discussionsupporting
confidence: 91%
“…Based on the individual differences in elderly patients with gynaecological malignant tumours, rehabilitation intervention based on the HBM can help patients fully understand the mechanism and severity and the importance of cooperative treatment and health exercise training for LEDVT and enhance their health beliefs and active participation consciousness. Postoperative rehabilitation training can effectively reduce the occurrence of deep vein thrombosis (DVT) [ 34 ]. One-on-one guidance from the intervention nurse can promote the patients' transition from passive exercise to active routine exercise, improve the prognosis of patients, and effectively reduce the incidence of LEDVT [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For patients with risk factors for PONV, including the female sex, a history of motion sickness or previous PONV, a nonsmoking status, and the use of postoperative opioid drugs, therapies should be given to decrease the occurrence or severity of PONV and postoperative OH. Early postoperative exercise, including lower limb strength training, is an essential component of rehabilitation protocols following posterior spinal fusion surgeries and can improve function and shorten the hospital stay (21)(22)(23). According to our ndings, better patient education of early postoperative ambulation to encourage patients to perform early postoperative out-ofbed exercises and postoperative strategies to increase the mobility of the lower limbs may be helpful to decrease the incidence of postoperative OH following posterior spinal fusion surgeries for the treatment of adolescent spinal deformities.…”
Section: Discussionmentioning
confidence: 99%